2020
DOI: 10.3390/cells9081774
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of PK11195 and Protoporphyrin IX Can Modulate Chronic Alcohol Intoxication in Rat Liver Mitochondria under the Opening of the Mitochondrial Permeability Transition Pore

Abstract: Decades of active research have shown that mitochondrial dysfunction, the associated oxidative stress, impaired anti-stress defense mechanisms, and the activation of the proapoptotic signaling pathways underlie pathological changes in organs and tissues. Pathologies caused by alcohol primarily affect the liver. Alcohol abuse is the cause of many liver diseases, such as steatosis, alcoholic steatohepatitis, fibrosis, cirrhosis, and, potentially, hepatocellular cancer. In this study, the effect of chronic alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 84 publications
(110 reference statements)
4
16
0
Order By: Relevance
“…Moreover, our studies and the work of other groups have shown the direct involvement of mPTP in the mechanisms acting in the mitochondria in chronic alcoholism [ 8 , 10 , 11 ]. It is known that the effect of alcohol in the mitochondria of the liver triggers the opening of mPTP [ 7 , 11 ].…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…Moreover, our studies and the work of other groups have shown the direct involvement of mPTP in the mechanisms acting in the mitochondria in chronic alcoholism [ 8 , 10 , 11 ]. It is known that the effect of alcohol in the mitochondria of the liver triggers the opening of mPTP [ 7 , 11 ].…”
Section: Introductionsupporting
confidence: 64%
“…Moreover, our studies and the work of other groups have shown the direct involvement of mPTP in the mechanisms acting in the mitochondria in chronic alcoholism [ 8 , 10 , 11 ]. It is known that the effect of alcohol in the mitochondria of the liver triggers the opening of mPTP [ 7 , 11 ]. We also obtained data about the existence of a new mechanism in rat liver mitochondria (RLM) in response to degenerative changes caused by ethanol that includes changes in the functioning of mPTP, the level of key regulators of mPTP and is possibly regulated by protein kinases [ 11 ].…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations